Aluminum plasmonic nanoshielding in ultraviolet inactivation of bacteria - Jeremy N. Kunz (Nature Portfolio, 2017)
Abstract Ultraviolet (UV) irradiation is an effective bacterial inactivation technique with broad applications in environmental disinfection. However, biomedical applications are limited due to the low selectivity, undesired inactivation of beneficial bacteria and damage of healthy tissue. New approaches are needed for the protection of biological cells from UV radiation for the development of controlled treatment and improved biosensors. Aluminum plasmonics offers attractive opportunities for the control of light-matter interactions in the UV range, which have not yet been explored in microbiology. Here, we investigate the effects of aluminum nanoparticles (Al NPs) prepared by sonication of aluminum foil on the UVC inactivation of E. coli bacteria and demonstrate a new radiation protection mechanism via plasmonic nanoshielding. We observe direct interaction of the bacterial cells with Al NPs and elucidate the nanoshielding mechanism via UV plasmonic resonance and nanotailing effects. Concentration and wavelength dependence studies reveal the role and range of control parameters for regulating the radiation dosage to achieve effective UVC protection. Our results provide a step towards developing improved radiation-based bacterial treatments.